The Impact of Interactive E-Modules on Students’ Understanding of Basic Map Knowledge in Geography Learning - Muhammad Ario Sya’bani; Nurul Azmi; Aisyah Trees Sandy; Yulian Widya Saputra (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examined the effectiveness of interactive e-modules in improving Grade X students’ learning outcomes in basic map knowledge at SMAN 2 Tenggarong Seberang. The research used a quantitative pre-experimental one-group pretest–posttest design involving 22 students. Data were collected through a 10-item multiple-choice test and analyzed using descriptive statistics, Shapiro–Wilk normality testing, paired sample t-test, and Cohen’s d. The mean pretest score was 63.82, while the posttest mean increased to 77.73. The paired sample t-test showed a significant difference between pretest and posttest scores (p = 0.006), and the effect size indicated a moderate impact (d = 0.657). These findings show that interactive e-modules are effective in supporting student-centered geography learning and improving students’ conceptual understanding of map symbols, scale, orientation, and interpretation. The study contributes evidence for developing digital geography instruction that is more interactive, flexible, and conceptually meaningful in secondary education. It also supports wider use of e-modules in visual geography topics strategically.